"As Your Heavenly Father is Perfect": The God of the Bible and Commandments in the Gospel. (October 2016) - Feldmeier, Reinhard
In common with much Hellenistic philosophy and Jewish tradition, early Christian writings often ground ethical teaching in the imitation of God. In the Gospels, however, what comes to the fore is "correspondence" to God, in which the divine love, mercy, and compassion provide the pattern also for human conduct. The bond of love between Creator and creature finds its most intimate expression in the relation of God as Father to God's children, a love that they are to embody in relations toward neighbor and enemy alike.